Mango Modulates Blood Glucose Similar to Rosiglitazone without Compromising Bone Parameters in Mice Fed High Fat Diet - Edralin A. Lucas; Angela Brown; Wenjia Li; Sandra K. Peterson; Yan Wang; Penny Perkins-Veazie; Stephen L. Clarke; Brenda J. Smith (Journal of Pharmacy and Nutrition Sciences, 2012)
Both consumption of high-fat diet and one of the commonly used pharmacological therapies for modulating blood glucose, rosiglitazone, are associated with negative effects on bone. Previously, we reported that a diet supplemented with freeze-dried mango modulated blood glucose similar to rosiglitazone in mice fed a high-fat (HF) diet. This study examined the effects of the addition of freeze-dried mango pulp or rosiglitazone to a HF diet on bone parameters in mice. Six week old male C57BL/6J mice were randomly assigned into one of five dietary treatment groups (n=8-9 mice/group): control (9.5% calories from fat), HF (58.9% calories from fat), HF+1% or 10% mango (w/w), and HF+rosiglitazone (50 mg/kg diet) for eight weeks. Bone parameters were assessed via dual energy x-ray absorptiometry and micro-computed tomography. Both the HF and HF+rosiglitazone groups had lower whole body, tibial, and vertebral bone mineral density compared to the HF+1% mango group. Trabecular bone volume, number, and separation as well as bone strength were also compromised by HF+rosiglitazone while the mango diets maintained these bone microarchitecture parameters to that observed in the control group. These results suggests that addition of mango to the diet may provide an alternative approach to modulating blood glucose without negatively affecting skeletal health, though human studies are needed to confirm these findings. Additionally, the bioactive component(s) in mango and the mechanisms by which it modulates blood glucose and exerts potentially osteoprotective benefits warrants further investigation.